Sexual and Gender Minority Health Research at the National Institutes of Health - Alexander, Rashada (LGBT Health, 2016)
Sexual and gender minority (SGM) populations experience many diseases and conditions at higher prevalence rates than their non-SGM counterparts. In 2009, the National Institutes of Health (NIH) commissioned an Institute of Medicine (IOM) report to better understand the health of SGM populations. Following the release of the report, NIH, including the National Cancer Institute (NCI), initiated new activities, and continued and expanded its existing efforts to advance the health of SGM individuals. Such efforts include various forms of outreach to solicit feedback, support of extramural researchers, analysis of the research portfolio to identify areas of opportunity, and the development of the NIH Strategic Plan for SGM Health Research.